Idiopathic chondrolysis of hip in children: New proposal and implication for radiological staging - Amarnath, C; Muthaiyan, Priya; Mary, T Helen; Mohanan, Shilpa; Gopinathan, K (Indian Journal of Radiology and Imaging, 2018)
Purpose: Our objective was to evaluate the radiological appearances in different stages of idiopathic chondrolysis of hip (ICH) which will be helpful in the early diagnosis and guiding appropriate treatment for this condition to prevent progression of disease. Materials and Methods: We evaluated 14 patients of ICH in varying stages: Stage 1 (n = 9), Stage 2 (n = 3), Stage 3 (n = 2). Average age at presentation was 10–11 years. Plain radiograph and magnetic resonance imaging (MRI) was done in all these patients. Results: In the current study, we have attempted to stage ICH based on the radiological progression of the disease, where MRI was used as the primary tool. Stage 1 showed a wedge-shaped hyperintensity in T2 weighted (T2W) and hypointensity in T1 weighted (T1W) images involving the middle one-third of the femoral head and it is the earliest and characteristic finding in MRI. Associated findings like joint space narrowing, synovial hypertrophy with joint effusion may also be observed. Stage 2 showed acetabular edema in the affected hip in addition to the above-mentioned findings. Stage 3 showed more extensive involvement of femoral head and acetabulum, with collapse of the femoral head, degenerative changes in hip, early osteoporotic changes, and ultimately loss of joint space. Conclusion: Imaging-based staging system proves very useful in the early diagnosis, staging, and assessing the prognosis of ICH.
Keywords: Femoral head and acetabulum; idiopathic chondrolysis of hip; radiological staging